Repeated short cycles of nonsteroidal anti-inflammatory drugs and kidney injury in patients with spinal degenerative-dystrophic diseases - D. M. Bichurina; I. Z. Gaydukova; D. А. Patrikeeva; A. P. Rebrov (Современная ревматология)
Objective: to evaluate kidney function in patients with spinal degenerative-dystrophic diseases (SDDDs) who take nonsteroidal anti-inflammatory drugs (NSAIDs) as repeated short cycles of treatment for severe back pain.Patients and methods. The investigation enrolled 97 patients with SDDDs who took NSAIDs for back pain (a study group). A control group consisted of sexand age-matched healthy individuals who had not used NSAIDs within the past year (n=40). Glomerular filtration rate (GFR) was estimated using the CKD-EPI equation and markers of kidney injury (albuminuria and globulinuria) were measured.Results. In the study group, GFR was decreased to <90 ml/min/1.73 m2 in 61 (62.9%) patients, to <60 ml/min/1.73 m2 in 11 (11.3%); the mean GFR was 77.5 [68.0; 89.0] ml/min/1.73 m2; in the control group, a decline in GFR to 89–60 ml/min/1.73 m2 was recorded in 35 (62.5%) cases; this indicator was >90 ml/min/1.73 m2 in the remaining 15 (37.5%) cases; the mean GFR was 82.5 [70.8; 90.0] ml/min/1.73 m2 (p≥0.05 for all pairwise comparisons). A decrease in GFR to <60 ml/min/1.73 m2 was found in 11 (11.3%) patients in the study group and in nobody in the control group (p=0.026). Elevated albuminuria was noted in 74 (76.3%) patients with SDDDs and in 9 (22.5%) healthy individuals (p<0.05). Albumin/creatinine ratio was 57.1 [33.8; 82.4] mg/g in the study group and 25.0 [17.5; 32.9] mg/g in the control group (p<0.0001). Increased globulinuria was established in all the patients with SDDDs and only in 3 (7.5%) healthy examinees. Globulin/creatinine ratio was 134.7 [77.5; 197.7] mg/g in the study group and 12.9 [0.5; 18.1] mg/g in the control group (p<0.0001).Conclusion. A decline in GFR to <60 ml/min/1.73 m2 was more often seen in the patients taking NSAIDs for spine pain caused by SDDDs than in the healthy individuals. In case of comparable GFR, the level of kidney injury markers was significantly higher in the study group than that in the control group, which suggests that patients with SDDDs who take NSAIDs have subclinical tubulointerstitial and glomerular changes.